"Dialog" jako wartość społeczno-kulturowa (na przykładzie "Tygodnika Powszechnego" z roku 1989) = "Dialogue" as a socio-cultural value (on the example of "Tygodnik Powszechny", 1989) - Kaczor, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The ways of understanding the dialogue revealed in the analysed articles of the press articles published in the 1989 "Tygodnik Powszechny" lead to several conclusions. Firstly, the language of discussion reflects dialogue as a necessity and a duty of social morality. Secondly, in the interpersonal dialogue, the norms and values expressed in relation to social reality are important. Third - dialogue helps to learn moral behaviour and justifies moral behaviour. Fourthly, dialogue clearly connects the community together.
Keywords: dialog; etyka społeczna; moralność; komunikacja międzyludzka; dialogue; social ethics; morality; interpersonal communication